Acid-catalyzed rearrangement of tetrahydrotricyclopentadiene for synthesis of high density alkyl-diamondoid fuel. (1st March 2019) - Xie, Jiawei; Zhang, Xiangwen; Xie, Junjian; Xu, Jisheng; Pan, Lun; Zou, Ji-Jun
Graphical abstract: Highlights: A facile route to synthesize alkyl-diamondoid fuel is developed. Reaction is conducted at low-dosage (∼10 wt%) and solvent-free. A significant high yield of 85.6% is achieved. Diamondoids have both high density (0.976 g/mL) and low freezing point (<−70 °C). Abstract: Alkyl-diamondoid fuels are attractive for aerospace vehicles due to their high energy density and supreme low-temperature performance. Here we reported a facile route to synthesize alkyl-diamondoids via solvent-free rearrangement of tetrahydrotricyclopentadiene simply catalyzed by acid. The reaction conditions including catalysts, temperature, catalyst dosage, and solvent were optimized. Notably, under the optimal conditions (10.7 wt% cat., 180 °C, 20 h) an extremely high content of alkyl-diamondoids (85.6%) was found in liquid phase, with high carbon yield of alkyl-diamondoids (60.0%) was obtained. The reaction kinetics of rearrangement has been investigated, and the reaction rate constants and apparent activation energies were calculated based on the experimental kinetic data. The resultant diamondoid-based product shows excellent low-temperature performance and a higher energy content than reported diamondoids and widely used JP-10 fuel, thus is superior as a high-energy-density fuel.